A risk reduction approach for academic research labs: A case study on naphthenic corrosion. (March 2020) - Stocco da Silva, Luís Henrique; Abreu Rodrigues, Luiz Carlos de; Nunes Diogenes, Alysson; Tedeschi Gomes Abrantes, Ana Carolina; Baptista, Adalberto; de Araújo Ponte, Haroldo
Abstract: Academic research and development (R&D) labs are a significant part of academic life. But there can be physical, environmental, and experiment quality risks associated to this activity. Academic labs can present specific experiments, which have associated risks for researchers. Academic labs are also characterized by a high turnover of students and many of them are not fully aware of the level of physical and environmental risks of their activity. Accidents in academic labs with injuries and loss of life are facts that have to be tackled through risk management approaches. The objective of this paper is to present an integrated management approach, tackling risk management and analysis methods. HAZOP (Hazard and Operability Study) and PFMEA (Process Failure Mode and Effects Analysis) enabled, respectively, the analysis of safety and environmental risks. By quantifying the level of risk according to the type of experiment and the research context, it is possible to provide safety to the system. The resulting Digital Poka-Yoke – a mistake-proofing approach – has brought about the desired quality of results in experiments. The proposed approach was validated through a case study monitoring naphthenic corrosion experiments conducted by the Lab of Surface Electrochemistry and Corrosion (LSEC) at the Federal University of Paraná (UFPR). As a consequence, this approach is currently in use at this lab. Highlights: Due to high turnover in academic labs, users may not be aware of involved risks. Labs accidents can be life-threatening and risk-preventing approaches must be used. Integrated HAZOP and PFMEA approaches enable safety and quality risk analysis. The approach results in a Digital Poka-Yoke to minimize academic lab risks.